Programas de triagem auditiva em crianças com doenças infecto contagiosas - Fontana, Ana Cláudia (2007)
Introduction: Identification of hearing loss in the first years of life favors rehabilitation in appropriate age ensuring the development of auditory function and consequent improvement in life quality. Major myelinization of nervous fibers occurs in life outside the womb when the child is more susceptible to consequences of a disease. It is important to follow up the development of these children in this period of life: in some cases hearing loss (caused by a disease or genetic) may appear during growth. Especially some diseases which affect mothers during pregnancy may be the cause of late installation. of Mother-child transmission communicable diseases like toxoplasmosis, citumegaloviruses, rubella, lues and herpes are in this group. Objective: this research aims to accomplish a literature review on hearing screening in children affected by congenital communicable diseases. Methods: to present the results obtained from studies on infant hearing screening especially on sensibility and specificity in children with congenital communicable diseases. Results: The methods used in newborn hearing screening between 1944 and 1970 were behavioral and led to a high number of false positive and false negative. Other procedures were developed in the search for objective and less subject to interpretation methods: cortical auditory evoked potentials and crib-o-gram. In the 1990´s otoacoustic emissions and brainstem auditory evoked potentials were the most recommended and reliable procedures used to this end. These recommendations led to the creation of a number of universal newborn hearing screening protocols in order to introduce a more appropriate and reliable way of evaluating congenital and or late installation hearing loss. In Brazil this process was slower for until 1995 behavioral techniques were still the most used to evaluate hearing in children. However, from this time on otoacoustic emissions were included in newborn hearing screening protocol. This way, eletrophysiologic procedures were added to newborn hearing screening. Conclusion: Nowadays in Brazil, otoacoustic emissions are widely used in newborn hearing screening. But, there is still much to implant in function of health investments and territorial extension. Therefore, a discussion on the adoption of a newborn hearing screening public health program and a review of determinant aspects in planning, efficiency, management and improvement of newborn public health has to be aimed. We confirmed several states in Brazil where there is a program from international and national literature. However, there is still necessity of implementation of new intervention programs. This will allow mainly a better prognosis in rehabilitation as well as audiologic follow up